KLASIFIKASI TIPE BERAT TUBUH MENGGUNAKAN METODE SUPPORT VECTOR MACHINE - Taufik Hidayatulloh; Lestari Yusuf (INTI Nusa Mandiri, 2023)
Abstract—The news of the death of a man in Indonesia is in the public spotlight because doctors have difficulty treating his illness because being overweight or obese causes the organs in the body to fail to function properly. Overweight causes the body to experience several health problems, including heart defects, diabetes, and several other diseases that can attack vital organs in the body. According to data on deaths caused by obesity, there are as many as 60 per 100,000 Indonesian population, and are a very feared killer. Faster handling of recognizing our body weight is important for each individual’s health. Classification can also help overweight in a person known more quickly. In this study, the classification algorithm that will be used is the Support vector machine (SVM). With 252 data, this study will use the SVM algorithm and look for the level of accuracy of the two classification classes, namely normal and overweight. This study produces an accuracy rate of 92.11% with a ROC curve value of 0.990 which means that the classification in this study is very good.